Estudo dos processos acadêmicos na Faculdade de Artes Visuais da UFG: proposta de melhoria por meio da ferramenta FMEA - Castilho, Gustavo Soares de (2019)
In a context of the demand of contemporary society for the provision of an agile and quality public service, focused on the results and needs of the citizen, public institutions face the inevitability of adapting themselves through the implementation of new technologies, modernization of their organizations and their work processes. The present research consists in the identification of the flaws and proposals for possible improvements in the agility of the academic processes that process in an academic secretariat of the Faculty of Visual Arts (FAV) of UFG, due to the absence of a detailed model in the institution. For this, the methodology used was the action research, of applied nature, qualitative-quantitative approach, and descriptive / explanatory objectives. The methodological procedure is an analysis of the processes and procedures performed in the secretariat, through process mapping tools and Failure Mode and Effect Analysis (FMEA) to identify failures, priorities for action and proposals for improvements. The objective of the research intervention was the creation of a manual of procedures of the academic processes in the FAV, from the mapping of the current situation carried out, that will serve as instruction document mainly to the servers of the unit. The realization of the mapping together with the FMEA was able to reach the proposed objectives, recommending its use in future works. The main flaws identified were delays in process analysis, lack of information to servers and students, and excessive procedures in the processes. Concerning the improvement proposals, suggestions were made for changes in legislation, stipulating deadlines for activities in the processes and the creation of instructive courses for teachers and administrative technicians, including audiovisual content also for students on how to proceed in academic processes. It was concluded that such proposals can optimize the work of the unit, by providing greater agility and quality in the service offered to the public.